Podjetniška demografija in značilnosti startup in scaleup podjetij: Slovenski podjetniški observatorij 2022 - Marina Bajić; Bradač Hojnik, Barbara (2023)
Business demographics and characteristics of startup and scaleup companies: Slovenian Entrepreneurship Observatory 2022. In the first part of the monograph, we analysed the business demography of Slovenian companies and compared it with European ones. The purpose of it is to get an insight into Slovenian companies and to understand how Slovenian entrepreneurship is placed in Europe. We analyzed the key characteristics of Slovenian companies and sole propretiors who engaged in entrepreneurial activities in 2021 and were classified in all SKD activities. In the second part of the research, we examined the characteristics of startup and scaleup companies. We focused primarily on studying their characteristics, needs and challenges, as those companies need the most support and incentives at the beginning of their development and during the transition to expansive growth. We studied their strategic importance, provided an international comparison of startup and scale-up companies, analysed the supporting environment for them and, based on primary research, provided key characteristics and recommendations for their support and development in Slovenia.
Keywords: companies; sole proprietors; financial performance indicators; startup companies; scaleup companies; strategies and policies; empirical analysis